Transmission of Information from Private to Public Markets - Chattopadhyay, Shrijata; McConnell, John J.; Trombley, Timothy E.; Yavuz, Mehmet Deniz (Journal of Financial and Quantitative Analysis, 2025)
We report evidence consistent with institutional investors using industry-level information that they obtain from their investments in venture capital (VC) funds to earn excess returns in publicly traded stocks. We use court rulings regarding the Freedom of Information Act as an exogenous shock affecting the information flow between VC funds and institutional investors to show that the excess returns are explained by information received via this channel. Thus, institutional investors serve as conduits of information from private to public markets. In the process, institutional investors earn higher returns from their VC investments than implied by the cash flows received therefrom.